Intussusceptive Vascular Remodeling Precedes Pathological Neovascularization. Issue 7 (July 2019) - Ali, Zaheer; Mukwaya, Anthony; Biesemeier, Antje; Ntzouni, Maria; Ramsköld, Daniel; Giatrellis, Sarantis; Mammadzada, Parviz; Cao, Renhai; Lennikov, Anton; Marass, Michele; Gerri, Claudia; Hildesjö, Camilla; et al.
Abstract : Objective—: Pathological neovascularization is crucial for progression and morbidity of serious diseases such as cancer, diabetic retinopathy, and age-related macular degeneration. While mechanisms of ongoing pathological neovascularization have been extensively studied, the initiating pathological vascular remodeling (PVR) events, which precede neovascularization remains poorly understood. Here, we identify novel molecular and cellular mechanisms of preneovascular PVR, by using the adult choriocapillaris as a model. Approach and Results—: Using hypoxia or forced overexpression of VEGF (vascular endothelial growth factor) in the subretinal space to induce PVR in zebrafish and rats respectively, and by analyzing choriocapillaris membranes adjacent to choroidal neovascular lesions from age-related macular degeneration patients, we show that the choriocapillaris undergo robust induction of vascular intussusception and permeability at preneovascular stages of PVR. This PVR response included endothelial cell proliferation, formation of endothelial luminal processes, extensive vesiculation and thickening of the endothelium, degradation of collagen fibers, and splitting of existing extravascular columns. RNA-sequencing established a role for endothelial tight junction disruption, cytoskeletal remodeling, vesicle- and cilium biogenesis in this process. Mechanistically, using genetic gain- and loss-of-function zebrafish models and analysis of primary human choriocapillaris endothelial cells, we determined that HIF (hypoxia-induced factor)-1α-VEGF-A-VEGFR2 signaling was important for hypoxia-induced PVR. Conclusions—: Our findings reveal that PVR involving intussusception and splitting of extravascular columns, endothelial proliferation, vesiculation, fenestration, and thickening is induced before neovascularization, suggesting that identifying and targeting these processes may prevent development of advanced neovascular disease in the future. Abstract : Supplemental Digital Content is available in the text.